Measuring the political policy development of the gig economy in Indonesia - Murdani, Andika Drajat; Wijayati, Hasna (The International Journal of Politics and Sociology Research, 2023)
Digital transformation has presented gig economy with its complexity.  In Indonesia, where technology is widely used, gig economy is viewed as a growth driver. Even so, there have been various dynamics from economic and political interests in the development of the gig economy. This research aims to analyze the political policies development of the gig economy in Indonesia, as Indonesian government response to developments in Indonesia's gig economy. The analysis was using qualitative research methods, with a library research approach. Data collected then interpreted and understood through descriptive and narrative analysis. The research found that the Indonesian government considers the gig economy is an opportunity for many workers. However, the government's response through its political policies seems inconsistent and only gave partial response based on the problems. The government wants to encourage the gig economy as an opportunity to advance the country's economy, such as through tax collection, and tried to provide a response and protection needs for gig workers. However, there are still regulatory limitations that cannot guarantee and protect the interests of the security and future of gig workers. In a political economy analysis, this condition shows the low level of sustainability in guarding the development of a gigantic economy.